The Influence of Cervical Spondylolisthesis on Clinical Presentation and Surgical Outcome in Patients With DCM: Analysis of a Multicenter Global Cohort of 458 Patients. Issue 4 (June 2020) - Nouri, Aria; Kato, So; Badhiwala, Jetan H.; Robinson, Michael; Mejia Munne, Juan; Yang, George; Jeong, William; Nasser, Rani; Gimbel, David A.; Cheng, Joseph S.; Fehlings, Michael G.
Study Design: Ambispective study with propensity matching. Objective: To assess the impact of cervical spondylolisthesis (CS) on clinical presentation and surgical outcome in patients with degenerative cervical myelopathy (DCM). Methods: A total of 458 magnetic resonance images (MRIs) from the AOSpine CSM-NA and CSM-I studies were reviewed and CS was identified. Patients with DCM were divided into 2 cohorts, those with CS and those without, and propensity matching was performed. Patient demographics, neurological and functional status at baseline and 2-year follow-up were compared. Results: Compared with nonspondylolisthesis (n = 404), CS patients (n = 54) were 8.8 years older ( P < .0001), presented with worse baseline neurological and functional status (mJOA [modified Japanese Orthopaedic Association Assessment Scale], P = .008; Nurick, P = .008; SF-36-PCS [Short Form–36 Physical Component Score], P = .01), more commonly presented with ligamentum flavum enlargement (81.5% vs 53.5%, P < .0001), and were less commonly from Asia ( P = .0002). Surgical approach varied between cohorts ( P = .0002), with posterior approaches favored in CS (61.1% vs 37.4%). CS patients had more operated levels (4.3 ± 1.4 vs 3.6 ± 1.2, P = .0002) and tended to undergo longer operations (196.6 ± 89.2 vs 177.2 ± 75.6 minutes, P = .087). Neurological functional recovery was lower with CS (mJOA [1.5 ± 3.6 vs 2.8 ± 2.7, P = .003]; Nurick [−0.8 ± 1.4 vs −1.5 ± 1.5, P = .002]), and CS was an independent predictor of worse mJOA recovery ratio at 2 years (B = −0.190, P < .0001). After propensity matching, improvement of neurological function was still lower in CS patients (mJOA [1.5 ± 3.6 vs 3.2 ± 2.8, P < .01]; Nurick [−0.8 ± 1.4 vs −1.4 ± 1.6, P = .02]). Conclusions: CS patients are older, present with worse neurological/functional impairment, and receive surgery on more levels and more commonly from the posterior. CS may indicate a more advanced state of DCM pathology and is more likely to result in a suboptimal surgical outcome.